Atomistic simulations of tungsten surface evolution under low-energy neon implantation. (2nd March 2016) - Backman, Marie; Hammond, Karl D.; Sefta, Faiza; Wirth, Brian D.
Abstract: Tungsten is a candidate material for the divertor of fusion reactors, where it will be subject to a high flux of particles coming from the fusion plasma as well as a significant heat load. Under helium plasma exposure in fusion-reactor-like conditions, a nanostructured morphology is known to form on the tungsten surface in certain temperature and incident energy ranges, although the formation mechanism is not fully established. A recent experimental study (Yajima et al 2013 Plasma Sci. Technol .15 282–6) using neon or argon exposure did not produce similar nanostructure. This article presents molecular dynamics simulations of neon implantation in tungsten aimed at investigating the surface evolution and elucidating the role of noble gas mass in fuzz formation. In contrast to helium, neon impacts can sputter both tungsten and previously implanted neon atoms. The shorter range of neon ions, along with sputtering, limit the formation of large bubbles and likely prevents nanostructure formation.